Assembly of 5H-dibenzo[a, d]cycloheptenes by a formal [5 + 2] annulation of ortho-aryl alkynyl benzyl alcohols with arenes. Issue 36 (2nd September 2022) - Zhang, Zhebing; Cai, Tao; Zhan, Zhaohui; Xu, Huiting; Yu, Lemao; Luo, Xiang; Li, Chunmei; Gao, Yuzhen; Wei, Xuemei; Chen, Xinzhi; Shen, Runpu
Abstract : We developed a protocol for the preparation of valuable 5 H -dibenzo[ a, d ]cycloheptenes by a formal [5 + 2] annulation of ortho -aryl alkynyl benzyl alcohols with arenes. Structurally diverse 5 H -dibenzo[ a, d ]cycloheptenes were achieved in moderate to good yields. Abstract : A new synthetic methodology for the synthesis of 5 H -dibenzo[ a, d ]cycloheptenes from ortho -aryl alkynyl benzyl alcohols and arenes via a Tf2 O-mediated formal [5 + 2] annulation reaction has been achieved. From this transformation, structurally diverse 5 H -dibenzo[ a, d ]cycloheptenes were achieved in moderate to good yields. This transformation probably involves an intermolecular Friedel–Crafts-type alkylation and a subsequent intramolecular 7- endo-dig cyclization in one pot, highlighting the high efficiency, regioselectivity, and step-economy of this protocol.